Coronary Arteriographic Profile in Hypertrophic Cardiomyopathy - Hasan, ATM Iqbal; Haque, Harisul; Zaman, M Mustafa; Haque, KMHS Sirajul; Banerjee, Sajal Krishna; Siddique, Md Abu; Arzu, Jahanara; Sultan, Md Ashraf Uddin; Sheikh, Naveen; Maria, -; et al. (University Heart Journal, 2017)
Back Ground: Hypertrophic cardiomyopathy is genetically transmitted primary cardiac disease and an important cause of morbidity and sudden death in young people, including competitive athletes. Objectives: The study was designed to compare the CAG findings between normal subject and hypertrophic cardiomyopathy patients who required CAG. Methods: HCM was diagnosed by using diagnostic criteria (clinical, electrocardiography and echocardiography) defined by Western Working group. The study was carried out on 60 subjects of which 30 had hypertrophic cardiomyopathy, 30 age and sex control (normal subjects). Results: In comparison of control it was observed that HCM cases had significantly larger proximal left anterior descending (3.81+-0.64 vs 2.49+-0.61 P < 0.001), proximal left circumflex (3.29+-0.46 Vs 2.39+-0.60, p < 0.001) and proximal right coronary artery (3.15+-0.47 vs 2.49+-0.42, P < 0.001). Coronary artery stenosis were found in 5 cases of HCM and among them, single vessel disease was present in 3, double vessel disease in I and triple vessel disease in I cases. Conclusion: Coronary artery disease (CAD) associated with hypertrophic cadiomyopathy (HCM) is a complex clinical syndrome, difficult to diagnose clinically, that can reliably be recognized by coronary arteriography. University Heart Journal Vol. 11, No. 2, July 2015; 71-78